Kristina Gosselin: capstone - Gosselin, Kristina, artist and filmmaker (Colorado State University. Libraries, 2018)
The artist's statement: I love making different types of artworks under the same medium of Electronic Art. Coding, video game creating and making animations are some of the digital arts I have done and love to do. Over the years of growing as an artist I have put more thought into the content and meaning behind my works of art. Such as my video game "Microvlavi Warrior" from Spring 2018. My game was all about the intentional and unintentional means of finding a glitch, both by the developer and player. As the developer I made the glitches intentional but in a way that seemed unintentional because I made the player be the one to glitch up the game and they wouldn't know it until the end. I also like experimenting with animation and coding. Currently, I am making an animation throughout the uses of Processing and coding in "Circle of Chaos" using circles as a metaphor claiming the circle of life but in a way that is chaotic, like life is for many people. My performance piece "Awkward Panda" (named by a friend) was a class project. As more people did more of the generic performance piece, I took a more energetic and fun outlook to the piece and used one of my friends as a model to have fun while filming. I believe art should not only be about making relative content and meaning but be about having fun during looking at the art as the audience member and during the process of making art as the creator.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Electronic distraction has no audio, the other videos have no spoken word.